Fabrication of transparent titanium dioxide thin film at low temperature by Sol-gel Spin Coating Method - Ahmad, Mohd Khairul
Titanium Dioxide (TiO2) thin film with various sol-gel concentrations has been successfully prepared using sol-gel spin coating method. The preparation of the TiO2 thin films was prepared at room temperature. The electrical and optical properties were characterized using 2- point probe I-V measurement and UV-Vis-NIR Spectrophotometer. For electrical properties, 0.2M of sol-gel concentration gives the lowest sheet resistance among other concentrated sol-gels. The optical transmission in the visible region (450– 1000 nm) for 0.1M and 0.2M are the highest (>80%), indicating that the films are transparent in the visible region. The transmission decreases sharply near the ultraviolet region due to the band gap absorption. The prepared TiO2 thin film can be used in many applications such as solar cell application, sensors and Ultra Violet coatings.